The Effect of PSAK 71 Implementation on the Quality of Financial Reporting in Banking Companies in Indonesia (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study analyzes the impact of the implementation of Financial Accounting Standards Statement (PSAK) 71 on the quality of financial reporting in the Indonesian banking sector. PSAK 71, which came into effect on January 1, 2020, adopts International Financial Reporting Standards (IFRS) 9 on financial instruments. The study used a quantitative approach with a sample of 43 banks listed on the Indonesia Stock Exchange for the 2019-2022 period. Financial reporting quality variables were measured using value relevance, earnings quality, and disclosure quality. The results showed that the implementation of PSAK 71 had a significant positive effect on the quality of banking financial reporting with a coefficient value of 0.542 and a significance level of 0.001. The improvement in quality was primarily seen in the more accurate measurement of expected credit loss (ECL) and improved transparency of credit risk information.
Keywords: PSAK 71; quality of financial reporting; banking, financial; instruments; expected credit loss